Data mining methods for gene selection on the basis of gene expression arrays - Muszyński, Michał; Osowski, Stanisław (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents data mining methods applied to gene selection for recognition of a particular type of prostate cancer on the basis of gene expression arrays. Several chosen methods of gene selection, including the Fisher method, correlation of gene with a class, application of the support vector machine and statistical hypotheses, are compared on the basis of clustering measures.
Keywords: gene expression array; gene ranking; feature selection; clusterization measures; fusion; SVM classification